Joyce's Book of Memory : The Mnemotechnic of Ulysses - Rickard, John S. (Book collections on Project MUSE., 1999)
Discusses Ulysses arguing that through the operation of memory, it mimics the working of the human mind and achieves its status as one of the most intellectual achievements of the 20th century.